Computed tomography scan imaging in case of destroyed lung post-tuberculosis - Arjana, Pande Nyoman; Sitanggang, Firman Parulian; Margiani, Ni Nyoman (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Destroyed lung is a radiological term describing severe and irreversible damage to the lung parenchyma, most commonly resulting from TB. This condition poses significant clinical challenges and requires advanced imaging for timely diagnosis and appropriate management. Case Presentation: This report presents three cases illustrating the clinical and radiological features of destroyed lung secondary to tuberculosis. The first case involves a 45-year-old woman with a prior history of TB who presented with facial swelling, dyspnea, and chronic cough; imaging revealed extensive cavitary lesions and destruction of the left lung. The second case describes a 25-year-old man with active TB who experienced worsening shortness of breath and night sweats; CT imaging showed a left fluidopneumothorax, multiple bullae, and bilateral cavitary lesions, indicating destroyed lung with secondary infection. The third case features a 46-year-old woman with chronic respiratory symptoms and right-sided pleural effusion; imaging demonstrated right lung destruction, bilateral fibrotic changes, and pulmonary artery hypertension. Conclusion: Destroyed lung remains a significant post-tuberculosis complication requiring prompt diagnosis and multidisciplinary management. Radiologists play a critical role in identifying characteristic imaging findings and reviewing prior imaging to support clinicians in developing appropriate treatment strategies.